Duodenal adenomatosis in familial adenomatous polyposis - Bülow, S (Copyright 2004 by Gut, 2004)
Background: The prevalence of duodenal carcinoma is much higher in familial adenomatous polyposis (FAP) than in the background population, and duodenal adenomatosis is found in most polyposis patients. Aims: To describe the long term natural history of duodenal adenomatosis in FAP and evaluate if cancer prophylactic surveillance of the duodenum is indicated. Methods: A prospective five nation study was carried out in the Nordic countries and the Netherlands. Patients: A total of 368 patients were examined by gastroduodenoscopy at two year intervals during the period 1990–2001. Results: At the first endoscopy, 238 (65%) patients had duodenal adenomas at a median age of 38 years. Median follow up was 7.6 years. The cumulative incidence of adenomatosis at age 70 years was 90% (95% confidence interval (CI) 79–100%), and of Spigelman stage IV 52% (95% CI 28–76%). The probability of an advanced Spigelman score increased during the study period (p<0.0001) due to an increasing number and size of adenomas. Two patients had asymptomatic duodenal carcinoma at their first endoscopy while four developed carcinoma during the study at a median age of 52 years (range 26–58). The cumulative incidence rate of cancer was 4.5% at age 57 years (95% CI 0.1–8.9%) and the risk was higher in patients with Spigelman stage IV at their first endoscopy than in those with stages 0–III (p<0.01). Conclusions: The natural course of duodenal adenomatosis has now been described in detail. The high incidence and increasing severity of duodenal adenomatosis with age justifies prophylactic examination, and a programme is presented for upper gastrointestinal endoscopic surveillance.